Dakwah Jama’ah Tabligh dalam Perspektif Psikologis - Siti Zulaiha (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2016)
Jama’ah Tabligh/Tablighis ( "Group informer") (Arabic: جماعة التبليغ , also called Tabliq) is an Islamic missionary movement with the aim of returning to the teachings of Islam as true. The main objective of this movement is to raise the spiritual soul in self and life of every Muslim to revive the deeds (tradition) which according to their perception has been exemplified by the Prophet and the scholars in the past. This article tries to explore the activity Jama’ah Tabligh/Tablighis of the psychological aspects of their members in the transformation of the Islamic values, religious person because attitudes also influence the attitudes and behavior of people. This paper also reveals how the ritual doctrines taught and religious activities conducted by Jama’ah Tabligh/Tablighis can shape the attitudes and followers behaviors, to discuss the authors use a psychological perspective.